Pengaruh Metode Jarimatika terhadap Kemampuan Berhitung Siswa Kelas II di SD - Yefri Yefri; Misdalina Misdalina; Tanzimah Tanzimah (Journal on Education, 2023)
This research is based on a problem, namely students' numeracy skills are still low, the method used only uses the lecture method. This study aims to determine the effect of the jarimatics method on the numeracy ability of grade II students in elementary schools and to determine the jarimatics method according to the characteristics of low-grade students. The research method used is an experiment with the type of true experimental design with the form of design used is posttest-only control design. The population used amounted to 44 students and the sample amounted to 44 students with a census sampling technique / total sampling. Data collection techniques use test and documentation techniques. Research analysis techniques used using t-test assisted by SPSS 26 software. Thus, it can be concluded that H_0 is rejected and H_a is accepted or there is a significant influence of the jarimatics method on the numeracy ability of grade II students in elementary school.